A kind of A-site redundant perovskite oxide and its preparation method and application
By introducing Sm ions at the A position, the A position is prepared by preparing the A position surplus perovskite oxide catalyst, the problem of high electrochemical overpotential of electrocatalytic OER materials is solved, the catalytic performance and stability are improved, and it is suitable for OER reactions in electrolyzed water.
Patent Information
- Application Number
- CN202411077440.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-08-07
AI Technical Summary
Existing electrocatalytic OER materials cannot meet the requirements of electrolytic water, especially because the electrochemical overpotential limits the water decomposition efficiency.
A perovskite oxide catalyst with A-position excess is prepared by introducing Sm ions at the A-position. The specific molecular formula is SmxSrCo0.95-m-nFemNinO3-δ, and the material is prepared by sol-gel method or high-temperature solid phase method.
The electrochemical performance of the material is improved, the overpotential is reduced, the current density is improved, and the catalytic stability is enhanced, so that it can show good OER catalytic performance in electrolyzed water.
Smart Images

Figure CN118954632B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalysis, and in particular relates to an A-site-rich perovskite oxide and a preparation method and application thereof. Background Art
[0002] Due to the excessive use of fossil energy, serious environmental pollution and energy shortage have been caused, which has led to the continuous growth of demand for clean energy and renewable energy, making researchers more actively seek and develop sustainable clean energy to gradually replace unsustainable and rapidly consumed fossil energy. Hydrogen energy is recognized as the most promising energy carrier in the future for its significant advantages such as clean and pollution-free, safe and convenient storage and transportation, wide application, less restricted by natural conditions, high efficiency, economy and renewability. Among various hydrogen production methods, electrochemical water decomposition is considered to be an effective and environmentally friendly way to produce high-purity hydrogen. However, due to the excessively high electrolysis potential, the oxygen evolution reaction (OER) strongly limits the efficiency of water decomposition. Precious metal-based catalysts (such as IrO2, RuO2) have shown excellent OER performance, but their own high cost, scarcity and poor stability limit their wide application. Therefore, finding and developing cheap, efficient and stable OER catalysts has become a research hotspot and urgent task in the current scientific research community.
[0003] In recent years, non-precious metal-based perovskite oxides have become an important part of the OER catalyst family due to their economic, abundant earth content and environmental friendliness. The basic structure of perovskite oxides is represented by ABO3, in which the A-site ions are tightly bound to oxygen in a twelve-coordinated form, often occupied by alkaline earth metals or rare earth elements; while the B-site ions form a hexacoordinate structure with oxygen, usually composed of transition metal elements such as Mn, Fe, Co, Ni, etc. One of the most significant features of the perovskite structure is its high plasticity and controllability. This structure can accommodate almost the entire range of elements in the periodic table to form a rich variety of oxide materials. What is particularly critical is that both the A-site and B-site ions of perovskite can be flexibly replaced partially or completely by other metal ions. This flexible ion replacement mechanism gives researchers the ability to precisely control their electronic structure, crystal morphology and surface chemical properties, thereby deeply optimizing their catalytic performance. Therefore, it is of great significance to develop high-performance OER catalysts based on perovskite structures.
[0004] So far, perovskite oxides with A-site cation defects have been widely studied, in which the charge compensation mechanism is often achieved through the formation of oxygen vacancies rather than the oxidation of low-valent ions. These additional oxygen vacancies are expected to improve the ionic conductivity and redox catalytic performance of the material. However, compared with the research boom on A-site defects, there are relatively few studies on perovskite materials with excess A-site cations. By finely regulating the excess degree of A-site cations, the electronic structure and crystal structure of the perovskite, as well as its surface chemical properties, can be further optimized, thereby showing better performance in OER, including reducing overpotential, increasing current density and enhancing catalytic stability. Therefore, strengthening the research on A-site excess perovskite electrocatalysts is of great significance for promoting the development of clean energy technologies. Summary of the invention
[0005] The present invention proposes a perovskite oxide with a surplus A position and a preparation method and application thereof to solve the problem that the existing electrocatalytic OER materials cannot meet the requirements of water electrolysis. 0.95-m-n Fe m Ni n O 3-δ The excess Sm in the base A position can improve the electrochemical properties of the material, making the material Sm x SrCo 0.95-m-n Fe m Ni n O 3-δ Can be better used in electrolyzed water.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A perovskite oxide with abundant A-position, the molecular formula is: Sm x SrCo 0.95-m-n Fe m Ni n O 3-δ ; Wherein, 0≤x≤0.2, 0≤m≤0.95, 0≤n≤0.95, 0<δ<1.
[0008] Furthermore, 0≤x≤0.2, 0≤m≤0.5, 0≤n≤0.5, 0<δ<1.
[0009] There are two methods for preparing the A-site-rich perovskite oxide of the present invention, namely, a sol-gel method and a high-temperature solid-phase method.
[0010] The sol-gel method includes the following steps: weighing raw materials according to the stoichiometric ratio, dissolving metal nitrate in deionized water, recorded as solution A; dissolving ethylenediaminetetraacetic acid and citric acid in water, then adding ammonia solution, stirring until clear, recorded as solution B; transferring the B solution to the A solution, adjusting the pH value of the solution, heating and stirring until a viscous dark purple gel is formed, and drying to obtain a solid precursor; calcining the solid precursor to obtain a perovskite oxide with excess A position.
[0011] Furthermore, the molar ratio of the metal ions in the metal nitrate, ethylenediaminetetraacetic acid, citric acid, and ammonium ions in the ammonia solution is (1-2):(1-2):(2-4):(10-20), and the metal ions include Sm, Sr, Co, Fe, and Ni.
[0012] Furthermore, the drying temperature is 200-250° C., and the time is 5-10 h; the calcination temperature is 900-1100° C., and the time is 5-10 h.
[0013] The high-temperature solid phase method includes the following steps: weighing raw materials according to the stoichiometric ratio, adding a solvent to the metal oxide or metal carbonate for ball milling, drying the obtained slurry to obtain a solid precursor, and calcining the solid precursor to obtain a perovskite oxide with excess A position.
[0014] Furthermore, the metal in the metal oxide or metal carbonate includes Sm, Sr, Co, Fe and Ni. The organic solvent is anhydrous ethanol.
[0015] Furthermore, the ball milling time is 5-10 hours; the calcination temperature is 900-1100° C. and the time is 10-20 hours.
[0016] The ionic radius of Sm is smaller than that of Sr. This difference may adjust the lattice structure of perovskite after doping, so that the crystal structure of the material is transformed into a pure cubic phase structure, reducing lattice distortion. In addition, the doping of Sm may change the electronic structure of B-site elements (such as Co, Fe, and Ni) in perovskite, enhancing the covalency of the BO bond. This enhancement of covalency is conducive to improving the material's adsorption capacity for oxygen or other reactants, thereby optimizing catalytic performance.
[0017] The present invention also provides an application of the A-position-rich perovskite oxide in an oxygen evolution reaction.
[0018] The present invention also provides a use of the A-site-rich perovskite oxide as an electrocatalytic working electrode material.
[0019] Compared with the prior art, the present invention has the following advantages and technical effects:
[0020] The present invention prepares a perovskite oxide catalyst with abundant A-site by introducing Sm ions at the A-site, thereby solving the problem of high electrochemical overpotential of the perovskite itself and greatly improving the catalytic performance.
[0021] When the electrocatalyst material of the present invention is used as an oxygen evolution electrocatalyst, the electrochemical oxygen evolution reaction performance test shows that the material has good catalytic performance at 10 mA / cm 2 When water is electrolyzed at a current density of , the overpotential is only 319 mV, making it an ideal OER electrocatalyst material with broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0023] Figure 1 The SrCo prepared in Example 1 0.45 Fe 0.45 Ni 0.05 O 3-δ -1 and Sm prepared in Example 5 0.1 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -1 X-ray diffraction curve (a); (b) is the local enlarged XRD graph of (a) at 32-34°;
[0024] Figure 2 The Sm prepared in Example 5 0.1 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -1 HR-TEM image and corresponding Fourier transform spectrum;
[0025] Figure 3 The SrCo prepared in Example 1 0.45 Fe 0.45 Ni 0.05 O 3-δ -1. Sm prepared in Example 3 0.05 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -1 and Sm prepared in Example 5 0.1 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ-1 as an OER electrocatalyst LSV performance test diagram; (a) IR-corrected LSV curve; (b) comparison diagram of the initial overpotential and overpotential;
[0026] Figure 4 SrCo prepared in Example 2 0.45 Fe 0.45 Ni 0.05 O 3-δ -2. Sm prepared in Example 4 0.05 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -2 and Sm prepared in Example 6 0.1 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -2 as an OER electrocatalyst LSV performance test diagram; (a) IR-corrected LSV curve; (b) comparison diagram of the initial overpotential and overpotential;
[0027] Figure 5 The Sm prepared in Example 5 0.1 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ Operational stability curve of -1 as an OER electrocatalyst. DETAILED DESCRIPTION
[0028] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0029] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0030] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0031] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0032] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0033] A perovskite oxide with abundant A-position, the molecular formula is: Sm x SrCo 0.95-m-n Fe m Ni n O 3-δ ; Wherein, 0≤x≤0.2, 0≤m≤0.95, 0≤n≤0.95, δ is the oxygen vacancy concentration, 0<δ<1. Preferably, 0≤x≤0.2, 0≤m≤0.5, 0≤n≤0.5, 0<δ<1, more preferably x=0.05-0.1, such as 0.05 or 0.1; m=0.45, n=0.05.
[0034] The present invention adds a small amount of Sm element as a surplus to SrCo 0.95-m-n Fe m Ni n O 3-δ The A-site Sr element greatly improves the electrochemical activity of OER electrocatalyst materials. This advantage makes Sm x SrCo 0.95-m-n Fe m Ni n O 3-δ It becomes an ideal material for OER electrocatalyst.
[0035] The A-rich perovskite oxide can be prepared by a sol-gel method or a high-temperature solid phase method. Both methods can obtain a pure cubic phase structure of Sm x SrCo 0.95-m-n Fe m Ni n O3-δ Electrocatalyst material powder, the specific technical solution is as follows:
[0036] The sol-gel method comprises the following steps: weighing raw materials according to the stoichiometric ratio, dissolving metal nitrate in deionized water, which is recorded as solution A; dissolving ethylenediaminetetraacetic acid and citric acid in water, then adding an ammonia solution, stirring until clear, which is recorded as solution B; transferring the B solution to the A solution, adjusting the pH value of the solution (ammonia can be used to adjust the pH value to 6-7, preferably pH=6.5), heating and stirring until a viscous dark purple gel is formed, and drying to obtain a solid precursor; placing the solid precursor in a muffle furnace and calcining to obtain a perovskite oxide with excess A position.
[0037] In the following preferred embodiments of the present invention, the molar ratio of the metal ions in the metal nitrate, ethylenediaminetetraacetic acid, citric acid, and ammonium ions in the aqueous ammonia solution is (1-2): (1-2): (2-4): (10-20), preferably 1: 1: 2: 10; the metal ions include Sm, Sr, Co, Fe, and Ni. The temperature of the heating and stirring is 80°C; the temperature of the drying is 200-250°C, the time is 5-10h, preferably drying at 250°C for 5h; the temperature of the calcination is 900-1100°C, the time is 5-10h, preferably calcining at 1000°C for 5h.
[0038] The high-temperature solid phase method includes the following steps: weighing raw materials according to the stoichiometric ratio, adding anhydrous ethanol to the metal oxide or metal carbonate for ball milling to obtain a slurry; placing the slurry in a forced air drying oven to dry, to obtain a solid precursor; placing the solid precursor in a muffle furnace to calcine, to obtain a perovskite oxide with excess A position.
[0039] In the following preferred embodiments of the present invention, the metal in the metal oxide or metal carbonate includes Sm, Sr, Co, Fe and Ni. The organic solvent is anhydrous ethanol. The ball milling time is 5-10h, and the ball milling speed is 400-500rpm, preferably 450rpm. The drying temperature is 80-100℃, the time is 5-10h, preferably dried at 85℃ for 5h. The calcination temperature is 900-1100℃, the time is 10-20h, preferably calcined at 1000℃ for 10h.
[0040] The A-site-rich perovskite oxide can be used in the oxygen evolution reaction in water electrolysis, and the A-site-rich perovskite oxide serves as an electrocatalyst in the oxygen evolution reaction in water electrolysis.
[0041] A method for preparing an electrocatalytic working electrode for OER comprises the following steps:
[0042] Sm x SrCo0.95-m-n Fe m Ni n O 3-δ , conductive carbon black, Nafion solution and anhydrous ethanol are mixed by ultrasonic treatment for 1-2 hours to form a slurry; the slurry is drop-coated on the surface of a glassy carbon electrode and dried in a natural state to obtain an electrocatalytic working electrode.
[0043] Before testing the electrochemical activity of the electrocatalyst, oxygen was introduced into the electrolytic cell for 40-60 minutes to ensure that the test was carried out under oxygen saturation. Then, the working electrode loaded with the electrocatalyst was pretreated by cyclic voltammetry. After the pretreatment, the OER catalytic performance was tested by a rotating disk electrode device (RDE). The test conditions are as follows:
[0044] Cyclic voltammetry (CV) test: scan rate 50-100 mV s -1 The scanning range is 0.1~-1.2Vvs.Ag / AgCl, and the CV scanning is not less than 20 cycles, and repeated CV curves appear.
[0045] Linear sweep voltammetry (LSV): scan rate 10-50 mV s -1 , the potential range is 0.2-1.0Vvs.Ag / AgCl, and the RDE speed is 1200-2000rpm.
[0046] Chronopotentiometry (CP) test: In 0.1-1M KOH electrolyte, fixed current is 5-10mAcm -2 , RDE speed is 1200-2000rpm.
[0047] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.
[0048] The raw materials used in the present invention are all purchased from the market.
[0049] The technical solution of the present invention is further illustrated by the following embodiments.
[0050] Example 1
[0051] Preparation of SrCo by a sol-gel method 0.45 Fe 0.45 Ni 0.05 O 3-δ -1(m=0.45, n=0.05), the specific steps are as follows:
[0052] Accurately weigh 4.2326g Sr(NO3)2(0.02mol), 2.6193g Co(NO3)2·6H2O(0.009mol), 3.636g Fe(NO3)3·9H2O (0.009 mol) and 0.291 g Ni(NO3)2·6H2O (0.001 mol) were dissolved in 100 mL of deionized water and stirred until clear, which was recorded as solution A. 11.69 g ethylenediaminetetraacetic acid (EDTA, 0.04 mol) and 15.37 g citric acid (CA, 0.08 mol) were dissolved in 50 mL of deionized water, and then 30.83 mL of ammonia solution with a mass concentration of 25% was added and stirred until clear, which was recorded as solution B. Solution B was drained with a glass rod and transferred to solution A, and then an appropriate amount of ammonia was added to adjust the pH value of the solution to 6.5, and heated and stirred at 80°C until a viscous dark purple gel was formed. The gel was further placed in a blast drying oven and dried at 250°C for 5 h to obtain a solid precursor. Finally, the solid precursor was calcined at 1000°C in a muffle furnace for 5 h to obtain SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -1 electrocatalyst powder (denoted as SCFN-1).
[0053] Example 2
[0054] A high temperature solid phase method for preparing SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -2(m=0.45, n=0.05), the specific steps are as follows:
[0055] The stoichiometric ratios of 2.953 g SrCO3 (0.02 mol), 0.718 g Fe2O3 (0.0045 mol), 0.7224 g Co3O4 (0.003 mol) and 0.0747 g NiO (0.001 mol) were accurately weighed, transferred to a ball mill in sequence, and 50 mL of anhydrous ethanol was added, and the mixture was ball milled at 450 rpm for 5 h to form a slurry with uniformly dispersed powders. After ball milling, the slurry was taken out with a dropper and transferred to a watch glass, which was placed in a forced air drying oven and dried at 85 ° C for 5 h to obtain a solid precursor. The solid precursor was then moved into a muffle furnace and calcined at 1000 ° C for 10 h to obtain SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -2 electrocatalyst powder (denoted as SCFN-2).
[0056] Example 3
[0057] A sol-gel method for preparing Sm 0.05 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -1(x=0.05, m=0.45, n=0.05), the specific steps are as follows:
[0058] Accurately weigh 0.444g Sm(NO3)3·6H2O (0.001mol), 4.2326g Sr(NO3)2 (0.02mol), 2.6193g Co(NO3)2·6H2O (0.009mol), 3.636g Fe(NO3)3·9H2O (0.009mol) and 0.291g Ni(NO3)2·6H2O (0.001 mol) was dissolved in 100 mL of deionized water and stirred until clear, which was recorded as solution A. 11.69 g of ethylenediaminetetraacetic acid (EDTA, 0.04 mol) and 15.37 g of citric acid (CA, 0.08 mol) were dissolved in 50 mL of deionized water, and 30.83 mL of ammonia solution was added and stirred until clear, which was recorded as solution B. Solution B was drained with a glass rod and transferred to solution A, and then an appropriate amount of ammonia solution was added to adjust the pH value of the solution to 6.5, and heated and stirred at 80°C until a viscous dark purple gel was formed. The gel was further placed in a forced air drying oven and dried at 250°C for 5 h to obtain a solid precursor. Finally, the solid precursor was calcined at 1000°C in a muffle furnace for 5 h to obtain Sm 0.05 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -1 electrocatalyst powder (denoted as S005SCFN-1).
[0059] Example 4
[0060] A high temperature solid phase method for preparing Sm 0.05 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -2(m=0.45, n=0.05), the specific steps are as follows:
[0061] Accurately weigh 0.1744 g Sm2O3, 2.953 g SrCO3, 0.718 g Fe2O3, 0.7224 g Co3O4 and 0.0747 g NiO in a stoichiometric ratio, transfer them to a ball mill in sequence, add 50 mL of anhydrous ethanol, and mill at 450 rpm for 5 h to form a slurry with uniformly dispersed powders; after ball milling, take out the slurry with a dropper and transfer it to a watch glass, place it in a forced air drying oven and dry it at 85 ° C for 5 h to obtain a solid precursor; then move the solid precursor into a muffle furnace and calcine it at a high temperature of 1000 ° C for 10 h to obtain Sm 0.05 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -2 electrocatalyst powder (denoted as S005SCFN-2).
[0062] Example 5
[0063] Same as Example 3, except that the amount of Sm(NO3)3·6H2O added was 0.889 g (0.002 mol), and Sm 0.1 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -1 electrocatalyst powder (denoted as S01SCFN-1).
[0064] Example 6
[0065] Same as Example 4, except that the amount of Sm2O3 added was 0.3487 g, and Sm 0.1 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -2 electrocatalyst powder (denoted as S01SCFN-2).
[0066] Figure 1 The SrCo prepared in Example 1 0.45 Fe 0.45 Ni 0.05 O 3-δ -1 (SCFN-1) and Sm prepared in Example 5 0.1 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ-1(S01SCFN-1); as can be seen from the figure, the diffraction peak intensity of S01SCFN-1 has no obvious change compared with SCFN-1, but the diffraction peak position shifts toward the large angle direction, proving that the Sr element site with a larger ionic radius is occupied by the Sm element with a smaller ionic radius, indicating that the Sm element has been well incorporated into the catalyst.
[0067] Figure 2 The Sm prepared in Example 5 0.1 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -1 HR-TEM image and corresponding Fourier transform spectrum; it can be seen from the figure that the (110) crystal plane with a lattice fringe plane spacing of 0.276nm can be clearly observed from the orderly arranged lattice array, which is close to the lattice spacing characteristic value corresponding to the (110) plane of the perovskite cubic phase. The corresponding Fourier transform spectrum reveals that the angle between the (110) and (100) crystal plane diffraction point arrangement directions is 90.18°, which is consistent with the standard cubic phase structure.
[0068] Application Example 1
[0069] The electrocatalysts prepared in Examples 1-6 were applied to OER to explore their electrocatalytic performance. The specific technical scheme is as follows: 10 mg of electrocatalyst powder, 10 mg of conductive carbon black, 0.1 mL of 5 wt.% Nafion solution and 1 mL of anhydrous ethanol were mixed by ultrasound for 1 hour to obtain a slurry, which was dripped onto the surface of the glassy carbon electrode and dried in a natural state, and then used as a working electrode. A three-electrode system was assembled for electrochemical testing. The test conditions are as follows:
[0070] 1) Cyclic voltammetry (CV) test: scan rate 100 mV s -1 , the scanning range is 0.1~-1.2Vvs.Ag / AgCl, 20 cycles of CV scanning are performed, and repeated CV curves appear.
[0071] 2) Linear Sweep Voltammetry (LSV): The electrochemical activity was determined by linear sweep voltammetry (LSV) using a CHI 760E electrochemical workstation at a scan rate of 10 mV s -1 , the potential range is 0.2-1.0Vvs.Ag / AgCl, and the RDE speed is 1600rpm.
[0072] 3) Chronopotentiometry (CP) test: At room temperature, oxygen was introduced into a 0.1 M KOH electrolyte to saturate the electrolyte with oxygen. The oxygen flow rate was controlled by a flow controller at 40 mL min -1, fixed current is 10mAcm -2 , RDE speed is 1600rpm.
[0073] The LSV electrochemical performance test of the electrocatalysts prepared by the sol-gel method used in Examples 1, 3 and 5 is as follows: Figure 3 As shown, the electrocatalyst prepared in Example 1 has an -2 The overpotential at 10 mA cm -2 The overpotential at 10 mA cm -2 The overpotential is 319 mV, which is lower than that of SrCo prepared in Example 1 and Example 3 under the same conditions. 0.45 Fe 0.45 Ni 0.05 O 3-δ -1 and Sm 0.05 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -1 for performance.
[0074] The LSV electrochemical performance test of the electrocatalysts prepared by the high temperature solid phase method used in Examples 2, 4 and 6 is as follows: Figure 4 As shown, the electrocatalyst prepared in Example 2 has an -2 The overpotential at 10 mA cm -2 The overpotential at 10 mA cm -2 The overpotential is 325 mV, which is lower than that of SrCo prepared in Example 2 and Example 4 under the same conditions. 0.45 Fe 0.45 Ni 0.05 O 3-δ -2 and Sm 0.05 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -2 performance.
[0075] Figure 3 and Figure 4 The results show that SSCFN can be used as an excellent OER electrocatalyst material, and it is found that under the same conditions, both the sol-gel method and the high-temperature solid-phase method can obtain electrocatalysts with excellent performance.
[0076] Stability is one of the key parameters to measure whether a catalyst can be used in industry. Figure 5The Sm prepared in Example 5 0.1 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -1 as an operational stability curve of OER electrocatalyst. It can be seen from the figure that Sm 0.1 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -1 still maintained a low potential after 20 hours of testing, which shows that Sm 0.1 SrCo 0.45 Fe 0.45 Ni 0.05 O 3-δ -1 is an excellent OER catalyst with good durability.
[0077] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A perovskite oxide with a surplus of A positions, characterized in that: Molecular formula: Sm x SrCo 0.95-m-n Fe m Ni n O 3-δ ; Wherein, x=0.05 or 0.1, m=0.45, n=0.05, 0<δ<1.
2. A method for preparing the A-rich perovskite oxide according to claim 1, characterized in that: The sol-gel method comprises the following steps: The raw materials are weighed according to the stoichiometric ratio, and the metal nitrate is dissolved in deionized water, which is recorded as solution A; ethylenediaminetetraacetic acid and citric acid are dissolved in water, and then an ammonia solution is added and stirred until clear, which is recorded as solution B; the solution B is transferred to solution A, the pH value of the solution is adjusted, and the solution is heated and stirred until a viscous dark purple gel is formed, and dried to obtain a solid precursor; the solid precursor is calcined to obtain a perovskite oxide with excess A position.
3. The method for preparing the A-rich perovskite oxide according to claim 2, characterized in that: The molar ratio of metal ions, ethylenediaminetetraacetic acid and citric acid in the metal nitrate is (1-2):(1-2):(2-4), and the metal ions include Sm, Sr, Co, Fe and Ni.
4. The method for preparing the A-rich perovskite oxide according to claim 2, characterized in that: The drying temperature is 200-250° C. and the time is 5-10 h; the calcining temperature is 900-1100° C. and the time is 5-10 h.
5. A method for preparing the A-rich perovskite oxide according to claim 1, characterized in that: The high temperature solid phase method is adopted, comprising the following steps: The raw materials are weighed according to the stoichiometric ratio, a solvent is added to the metal oxide or metal carbonate for ball milling, the obtained slurry is dried to obtain a solid precursor, and the solid precursor is calcined to obtain the A-site-rich perovskite oxide.
6. The method for preparing the A-rich perovskite oxide according to claim 5, characterized in that: The metal in the metal oxide or metal carbonate includes Sm, Sr, Co, Fe and Ni.
7. The method for preparing the A-rich perovskite oxide according to claim 5, characterized in that: The ball milling time is 5-10 hours; the calcination temperature is 900-1100° C. and the time is 10-20 hours.
8. Use of the A-site-rich perovskite oxide according to claim 1 in an oxygen evolution reaction.
9. Use of the A-site-rich perovskite oxide according to claim 1 as an electrocatalytic working electrode material.
Citation Information
Patent Citations
B-site vacancy Fe-doped strontium titanate and preparation method thereof
CN110483036A
Cation co-doped perovskite catalyst for oxygen evolution reaction and preparation method thereof
CN110860292A
Perovskite material with excessive A site, preparation method and application of perovskite material in catalytic treatment of organic wastewater
CN113231068A